2023
DOI: 10.3389/fnins.2022.1037895
|View full text |Cite
|
Sign up to set email alerts
|

A novel visual dynamic nomogram to online predict the risk of unfavorable outcome in elderly aSAH patients after endovascular coiling: A retrospective study

Abstract: BackgroundAneurysmal subarachnoid hemorrhage (aSAH) is a significant cause of morbidity and mortality throughout the world. Dynamic nomogram to predict the prognosis of elderly aSAH patients after endovascular coiling has not been reported. Thus, we aimed to develop a clinically useful dynamic nomogram to predict the risk of 6-month unfavorable outcome in elderly aSAH patients after endovascular coiling.MethodsWe conducted a retrospective study including 209 elderly patients admitted to the People’s Hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Lu et al. developed a nomogram that predicted the risk of 6‐month unfavorable outcomes (by the modified Rankin score) in older patients with aSAH after endovascular coiling 29 . Hu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al. developed a nomogram that predicted the risk of 6‐month unfavorable outcomes (by the modified Rankin score) in older patients with aSAH after endovascular coiling 29 . Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al developed a nomogram that predicted the risk of 6-month unfavorable outcomes (by the modified Rankin score) in older patients with aSAH after endovascular coiling. 29 Hu et al developed an online prediction tool based on a random forest model to identify patients at a high risk of delayed cerebral ischemia after aSAH. 30 Fang et al reported that elevated D-dimer levels on admission were associated with short-and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously used ones, dynamic changes in total tau in the cerebral microdialysate [ 17 ] and the CSF arginine/ornithine ratio are among the latest areas of interest [ 18 ]. An interesting online, visual dynamic nomogram has been proposed to predict the risk of adverse outcome at 6 months in elderly patients after undergoing endovascular therapy for aneurysmal SAH [ 19 ].…”
mentioning
confidence: 99%